Inhibition of bromodomain-containing protein 9 for the prevention of epigenetically-defined drug resistance. Issue 15 (1st August 2017) - Crawford, Terry D.; Vartanian, Steffan; Côté, Alexandre; Bellon, Steve; Duplessis, Martin; Flynn, E. Megan; Hewitt, Michael; Huang, Hon-Ren; Kiefer, James R.; Murray, Jeremy; Nasveschuk, Christopher G.; Pardo, Eneida; et al.
Graphical abstract: Abstract: Bromodomain-containing protein 9 (BRD9), an epigenetic "reader" of acetylated lysines on post-translationally modified histone proteins, is upregulated in multiple cancer cell lines. To assess the functional role of BRD9 in cancer cell lines, we identified a small-molecule inhibitor of the BRD9 bromodomain. Starting from a pyrrolopyridone lead, we used structure-based drug design to identify a potent and highly selective in vitro tool compound11, (GNE-375 ). While this compound showed minimal effects in cell viability or gene expression assays, it showed remarkable potency in preventing the emergence of a drug tolerant population in EGFR mutant PC9 cells treated with EGFR inhibitors. Such tolerance has been linked to an altered epigenetic state, and11 decreased BRD9 binding to chromatin, and this was associated with decreased expression of ALDH1A1, a gene previously shown to be important in drug tolerance. BRD9 inhibitors may therefore show utility in preventing epigenetically-defined drug resistance.